(untitled) - Wiiliam Bolton (London, 1994)
This book provides an essential introduction to the basic principles involved and is specifically. It gives a practical and comprehensive appreciation and understanding of the ways in which manafacturing companies are organized, the nature and diversity of engineering products, the organization of production, the planning and control of production. Each chapter includes revision questions and case problems with outlines of answers
Keywords: industrial management,production management,production planning